A zonal and segmentation analysis of the relationships between variations in sea-surface temperatures of the western Pacific Ocean and Southeast Asian rainfall. Issue 5 (12th August 2022) - Wangsomcholk, Chalermpol; Shrestha, Rajendra Prasad; Ninsawat, Sarawut; Winijkul, Ekbordin
Abstract: With the objective of understanding how terrestrial precipitation in Southeast Asia (SEA) responds to both temporal and spatial variations in sea-surface temperature (SST) of the western Pacific Ocean, we first used the North–South and zonal SST variation analyses for the data set named A Group for High-Resolution Sea-Surface Temperature (GHRSST) Level 4 Multiscale Ultrahigh Resolution (MUR). Second, we applied a localized correlation analysis to the SST data set and rainfall data (Integrated Multi-satellitE Retrievals for Global precipitation measurement (IMERG)) in order to determine the boundaries and characteristics of the complex interactions between SST and rainfall variations. The zonal SST variation analysis result suggested that the warm pool in the North of western Pacific zones close to SEA (120 °E–150 °E) was more sustained and less varied than that in the South zones. In terms of the western Pacific SST impact on rainfall in SEA, the correlation analysis confirmed the well-established concept that the SST of the ocean part close to the SEA land, in general, has more influence on SEA rainfall than does the SST of the ocean part far away from SEA. Still, there were some parts of SEA whose rainfall was not governed by the sea–land juxtaposition. HIGHLIGHTS: Change in SST in the western Pacific areas, in particular those situated close to the SEA region, might not bring about the uniform changes in precipitation throughout the entire region. Rainfall in some areas of the SEA region, albeit longitudinally close to the western Pacific, did not have the strongest correlation with SST, suggesting the limited influence of sea–land proximity. Graphical Abstract